Multiparameter flow cytometric and transcriptional analyis of CD20 positive T-cells in bone marrow in patients of multiple myeloma and monoclonal gammopathy of undetermined significance - Forró, Barbara; Kajtár, Béla; Lacza, Ágnes; Kereskai, László; Vida, Livia; Kőszegi, Balázs; Urbán, Péter; Kun, József; Gyenesei, Attila; Kosztolányi, Szabolcs; Kehl, Dániel; Jáksó, Pál (Frontiers in Immunology, 2025)
IntroductionCD20+ T-cells were described firstly in peripheral blood and later in bone marrow in patients with hematological tumors, and certain immune-mediated diseases. During our hematological diagnostic work, this peculiar subgroup of lymphocytes has been consistently observed associated with untreated monoclonal gammopathy of undetermined significance (MGUS) and myeloma (MM). Despite the expanding literature data, the exact function of CD20+ T cells remains unclear.MethodsWe investigated the incidence of CD20+ T-cells in MGUS (n=27), and MM using a larger cohort (n=125) and compared it with control bone marrow samples (n=39). We examined their presence before and after treatment in 32 cases with flow cytometry. Comprehensive flow cytometric analysis included the examination of functional (T-cell activation, cytotoxic molecules and T-cell exhaustion) and maturation markers in a large number of cases. In addition RNA sequencing and subsequent bioinformatics analyses were carried out to detect differentially expressed (DE) genes of FACS sorted CD20+ T-cells versus CD20- T-cells.Results and discussionWe found that CD20+ T-cells are phenotypically and transcriptionally different from CD20- T-cells. Elevated incidence of CD20+ T-cells in MGUS and MM and the expression of CD8, NKG2D, and CD28 suggests anti-tumor functionality. Increased PD-1 expression indicates T-cell exhaustion which was mostly detected in the samples of patients with a higher tumor percentage. The majority of CD20+ T-cells are effector or effector memory T-cells. Some of the differentially expressed genes suggest antitumor function via regulating T-cell activation pathways, while other genes involved in tumor escape from immune surveillance by suppressing T-cells or by reprogramming T-cells toward T-cell exhaustion. Our findings suggest that CD20+ T-cells may play a vital role both in immune surveillance and immune escape contributing to progression of multiple myeloma.